2009
DOI: 10.1002/bsl.897
|View full text |Cite
|
Sign up to set email alerts
|

The impact of outcome knowledge, role, and quality of information on the perceived legitimacy of lethal force decisions in counter‐terrorism operations

Abstract: According to the phenomenon of hindsight bias, once people know the outcome of an event, they tend to have biased estimates of the probability that the event would have occurred. In this study, we investigated whether hindsight bias affected judgements about the legitimacy of lethal force decisions in police shooting incidents for counter-terrorism operations. We also assessed to what extent this hindsight bias was mediated by factors such as role and information quality. Four hundred and eighty participants c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 35 publications
0
5
0
Order By: Relevance
“…However, the investigation of such incidents constitutes a major and high profile task both for police forces and external agencies such as the Independent Police Complaints Commissions (IPCC) established in the U.K. under the Police Reforms Act, 2002. Internationally, such investigations are typically high profile, attracting both public and media attention, and have serious consequences for the officers involved (Goodwill et al, 2010). Thus, the development of evidence-based policy and investigative practice is critical.…”
Section: Discussionmentioning
confidence: 99%
“…However, the investigation of such incidents constitutes a major and high profile task both for police forces and external agencies such as the Independent Police Complaints Commissions (IPCC) established in the U.K. under the Police Reforms Act, 2002. Internationally, such investigations are typically high profile, attracting both public and media attention, and have serious consequences for the officers involved (Goodwill et al, 2010). Thus, the development of evidence-based policy and investigative practice is critical.…”
Section: Discussionmentioning
confidence: 99%
“…The result may be wariness to accept new initiatives on the chance that an unforeseen event will arise that will produce future (hindsight-driven) blame. More to the point, hindsight bias heightens punitiveness, as demonstrated in numerous studies on hindsight bias in legal decisions, such as those made by jurors (Casper, Benedict, & Perry, 1989; Eberwine, 2005; Goodwill et al, 2010; Harley, 2007; Hastie et al, 1999; Kamin & Rachlinski, 1995; LaBine & LaBine, 1996; Smith & Greene, 2005).…”
Section: Consequences Of Hindsight Biasmentioning
confidence: 99%
“…Knowledge that is gathered later, such as from accident scene investigations, forensic tests, or the arbitrary discovery of an oddly misused product, is deemed irrelevant in evaluating the quality of the decisions made in the moment, that is, before a focal mishap occurred. As empirical studies have shown, however, hindsight bias routinely afflicts judgments of a defendant’s past conduct (e.g., Goodwill, Alison, Lehmann, Francis, & Eyre, 2010; Hastie, Schkade, & Payne, 1999; Kamin & Rachlinski, 1995; LaBine & LaBine, 1996; Smith & Greene, 2005; Stallard & Worthington, 1998). 3…”
mentioning
confidence: 99%
“…For example, in some countries, particularly in the UK, the decision to shoot or take lethal force against a suspect must be evaluated by a police commission to determine the reasonableness of the action given the circumstances (in all jurisdictions of which we are aware, an investigation occurs if a reasonable question is raised about an officer’s decision to use force). These evaluations should only concern the circumstances in which the decision was made, rather than the outcome to the officer’s conduct or information about the victim discovered after the fact; however, these evaluations may be influenced by HB (Goodwill, Alison, Lehmann, Francis, & Eyre, 2010; Villejoubert, O’Keeffe, Alison, & Cole, 2006).…”
Section: Resultsmentioning
confidence: 99%